Hybrid ZnO/TiO2 Loaded in Electrospun Polymeric Fibers as Photocatalyst. (6th December 2015) - Araújo, Evando S.; Libardi, Juliano; Faia, Pedro M.; de Oliveira, Helinando P.
Abstract : Hybrid ZnO/TiO2 nanoparticles were applied as potential photocatalyst agents incorporated into electrospun fibers of enteric block copolymers. The resistance of fibers avoids aggregation and contributes to prolonged action of semiconductor nanoparticles under continuous light irradiation. Such behavior is attributed to the minimal aggregation degree and elevated efficiency of photodegradation of modified nanoparticles in comparison with pristine ones. Hybrid ZnO/TiO2 in nanofibers contributes to the association of different mechanisms such as N-deethylation and cleavage of dye molecules applied in the overall process of photodegradation.